Pengaruh Metode Lauhun terhadap Kemampuan Menghafal Al-Qur’an Peserta Didik pada Mata Pelajaran Al Qur’an Hadits - Dwi Ahada; Marliat Marliat; Inti Pita Sari (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
This study aimed to analyze the implementation of the Lauhun method in Qur'an and Hadith learning, describe students' Qur'an memorization ability, and examine the effect of the Lauhun method on students' Qur'an memorization ability at MTs Nahdlotul Muslimin. The study employed a quantitative approach using an explanatory survey design. The population consisted of 265 students, while 73 respondents were selected through proportionate stratified random sampling. Data were collected using questionnaires, memorization tests, observations, and documentation, and were analyzed using descriptive statistics and the Chi-Square test at a 5% significance level. The findings revealed that the implementation of the Lauhun method was categorized as moderate, accounting for 60.27% of respondents. Likewise, students' Qur'an memorization ability was predominantly in the moderate category (60.27%). The hypothesis testing produced a Chi-Square value of 21.74, exceeding the critical value of 9.488, indicating that the alternative hypothesis was accepted. These findings demonstrate that the Lauhun method has a significant effect on students' Qur'an memorization ability. Better implementation of the Lauhun method is associated with higher levels of Qur'an memorization achievement. Therefore, the Lauhun method can serve as an effective instructional strategy for improving the quality of Qur'an and Hadith learning in Islamic junior secondary schools.